2021
DOI: 10.1590/1679-78256240
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Multiscale Finite Element Method (EMsFEM) Analysis of Periodic Truss Metamaterials (PTMM) Designed by Asymptotic Homogenization

Abstract: Asymptotic Homogenization (AH) and the Extended Multiscale Finite Element Method (EMsFEM) are both procedures that allow working on a structural macroscale that incorporates the effect of averaged microscopic heterogeneities, thus resulting in computationally efficient strategies. EMsFEM works directly on coupled finite micro and macroscales using numerically built discrete interpolation functions. Periodic Truss Metamaterials (PTMMs) are cellular materials formed by the periodic repetition of a truss-like uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Metamaterials (Mms) are often described as periodic arrangements organized into blocks that possess properties and functionalities differing and enhancing those of the constituent materials (Bertoldi et al, 2017;Xianglong et al, 2018;Guevara-Corzo et al, 2022;Jagiello and Muñoz-Rojas, 2021). Several studies can be found in the literature that explores appications in engineering and structural design (Fraternali et al, 2015;Gonçalves Salsa Junior et al, 2022;Comi and Driemeier, 2018;Rodrigues et al, 2019;between others).…”
Section: Auxetic Metamaterialsmentioning
confidence: 99%
“…Metamaterials (Mms) are often described as periodic arrangements organized into blocks that possess properties and functionalities differing and enhancing those of the constituent materials (Bertoldi et al, 2017;Xianglong et al, 2018;Guevara-Corzo et al, 2022;Jagiello and Muñoz-Rojas, 2021). Several studies can be found in the literature that explores appications in engineering and structural design (Fraternali et al, 2015;Gonçalves Salsa Junior et al, 2022;Comi and Driemeier, 2018;Rodrigues et al, 2019;between others).…”
Section: Auxetic Metamaterialsmentioning
confidence: 99%